Modernisation Factors of Infant Mortality Transition in Late Imperial Perm Province - Bakharev, Dmitry S. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2023)
This article studies urban infant mortality in the post-reform period of Perm Province. The work reconstructs the dynamics of infant mortality in cities and villages of the Middle Urals, highlighting the patterns of individual cities and identified factors of evolution. It is based on published state and zemstvo statistics, archival documents from medical institutions and public organisations, as well as Orthodox Church parish records from Ekaterinburg. Methodologically, the work relies on general demographic indices, descriptive statistics techniques, seasonality coefficients, and dynamic series analysis. During the first half of the nineteenth century, the mining Urals had extremely high birth and death rates and the highest infant mortality rate in European Russia. The Great Reforms launched the demographic transition in the region, resulting, among other things, in the Empire’s most significant infant mortality decline in the early twentieth century. The earliest and fastest infant mortality decline took place in cities. Small towns had slightly better rates than rural areas, while Perm and especially Ekaterinburg had significant reductions. The main reasons behind the changes in infant mortality were economic employment diversification, the weakening of ethno-religious traditions, and the creation of medical infrastructure. In daily life, these factors manifested in the smoothing of demographic seasonality, increased period between birth and baptism, the introduction of artificial nourishment with the help of glass feeding bottles and rubber comforters, and moving childbirths and infant care to hospitals. Ekaterinburg, the economic capital of the region, was the place where these factors had the best effect.